The Quest for an Ideal Beauty in Toni Morrison's The Bluest Eye - Maysoon Taher Muhi; Fatima Ridha (College of Education for Women, 2019)
In The Bluest Eye (1970), the American-African writer, Toni Morrison explores how Western standards of ideal beauty are created and propagated with and among the black community. The novel not only portrays the lives of those whose dark skinned and Negroid features blight their lives; it also shows how the standard of white beauty, when imposed on black youth, can drastically damage one's self-love and esteem which usually occurs when beauty goes unrecognized. Morrison in this novel focuses on the damage that the black women characters suffer through the construction of femininity in a racialised society where whiteness is used as a standard of beauty.